2020
DOI: 10.1007/s10995-020-02925-3
|View full text |Cite
|
Sign up to set email alerts
|

Matching Psychosocial Support Needs of Parents of a Child with a Chronic Illness to a Feasible Intervention

Abstract: Objectives Parents of children with a chronic illness (CI) are at risk for psychosocial problems. The aim of this study was to refine an existing face-to-face intervention into an online psychosocial group intervention for parents by (1) exploring which themes are important, (2) determine what type of intervention parents would like and (3) assess parents’ practical preferences. Methods Parents of children with a CI (0–18 years) were invited to complete an online questionnaire. To acquire more in-depth infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The present study found that parents of children with chronic illness reported lower level of family resilience compared to parents of healthy children. This result suggested that being diagnosed with childhood chronic illness is a stressful event that might weaken the ability of family as a whole to accommodate stressful events together (46)(47)(48). Parents of children with chronic illness also reported lower scores on the authoritative parenting compared to their counterparts in present study, which partially support the result of previous study that parents of children with chronic illness tended to be over-involved in children's lives, and their children were more likely to depend on their parents without autonomy (49).…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that parents of children with chronic illness reported lower level of family resilience compared to parents of healthy children. This result suggested that being diagnosed with childhood chronic illness is a stressful event that might weaken the ability of family as a whole to accommodate stressful events together (46)(47)(48). Parents of children with chronic illness also reported lower scores on the authoritative parenting compared to their counterparts in present study, which partially support the result of previous study that parents of children with chronic illness tended to be over-involved in children's lives, and their children were more likely to depend on their parents without autonomy (49).…”
Section: Discussionmentioning
confidence: 99%
“…The following sessions each focus on a theme: session (a) the CI of the child, (b) relationships within the family, (c) taking care of yourself, and (d) relationships with others and practical support (e.g., school of the child, work). In the sixth and last session there is time to repeat topics or to resume discussions that have not been finished due to lack of time ( Douma, et al., 2019a ). Coping skills were addressed in every session.…”
Section: Methodsmentioning
confidence: 99%
“…Considering this, an online psychosocial CBT/ACT group intervention called Op Koers Online (English: On Track Online ) for parents, focusing on parents themselves, was designed in close cooperation with parents. Parents were asked via an open access survey and focus groups what they would like in an intervention ( Douma et al., 2019a ). The intervention is partly based on the already existing Op Koers face-to-face intervention for children, adolescents and parents, which was proven to be effective ( Scholten et al., 2013 ), and on Op Koers Online for adolescents of which pilot studies showed promising results on feasibility and preliminary efficacy ( Douma et al., 2019b ; Maurice-Stam et al., 2014 ).…”
Section: Literature Overviewmentioning
confidence: 99%
“…These are leading to serious consideration of familycentered approaches targeting the mental wellbeing of caregivers as a pivotal factor to optimize children's health outcomes, such as treatment adherence [18][19][20]. Accordingly, cognitive behavioral therapy (CBT) and mindfulness-based cognitive therapy (MBCT) have demonstrated positive outcomes regarding stress and healthy quality of life of caregivers and children [21].…”
Section: Introductionmentioning
confidence: 99%